Plastics additives database - Flick, Ernest W.
Plastics additives are a group of minerals and chemical derivatives made by a large number of companies for a variety of applications. This database is a unique compilation of 7,000 additives with information from manufacturers and suppliers of these important products.
Keywords: Plastics -- Additives -- Tables.; elektronické knihy; electronic books